Technical Note: Characteristics of a microSilicon X shielded diode detector for photon beam dosimetry. Issue 4 (6th March 2021) - Akino, Yuichi; Okamura, Keita; Das, Indra J.; Isohashi, Fumiaki; Seo, Yuji; Tamari, Keisuke; Hirata, Takero; Hayashi, Kazuhiko; Inoue, Shinichi; Ogawa, Kazuhiko
Abstract : Purpose: This study investigated the characteristics of a new shielded diode detector, microSilicon X (model 60022: MSX), for small‐field and large‐field dosimetry. Methods: The percent depth dose (PDD), beam profiles, detector output factor ( OF det ), temperature dependence, dose rate dependence, dose‐per‐pulse (DPP) dependence, and dose‐response linearity of MSX were evaluated in Cyberknife and TrueBeam photon beams and compared with various detectors including microDiamond (PTW model 60019: MD), Sun Nuclear EDGE detector, Photon diode (PTW model 60016: PD), and semiflex ionization chamber (PTW model 31010: IC). Results: For field sizes ranging from 50 × 50 mm 2 to 400 × 400 mm 2, MSX‐measured OF det values were within 1% of the IC‐measured values. For the CyberKnife small fields, the maximum difference between the MSX‐measured OF det and the MD‐measured field output factor (Ω) was 4.0%, while the maximum differences were 8.8% and 10.9% for PD and EDGE, respectively. MSX showed a stable response within 0.7% for water temperatures of 5°C to 34°C, while PD and EDGE showed a linear correlation between the water temperature and the response. MSX showed small variations within 0.2% for the dose rate, and PD and EDGE showed logarithmic increases in the response with the dose rate. MSX and MD had smaller DPP dependences than PD and EDGE. Conclusions: The characteristics of MSX for measurements of small‐ and large‐field photon beams are favorable. Compared to PD, MSX exhibited significant improvement in the over‐response for small fields. The OF det values measured by MSX were approximately in‐between those measured by MD and PD. MSX showed stable responses against water temperature, dose rate, and DPP variations and provided suitable data for a wide range of field sizes. However, careful attention is required for measurements of OF det for field sizes of <10 × 10 mm 2 and PDD for field sizes of ≥200 × 200 mm 2 .